2017
DOI: 10.1053/j.ajkd.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Maintenance Immunosuppression Treatment of Proliferative Lupus Nephritis: A Network Meta-analysis of Randomized Trials

Abstract: Evidence for induction therapy for lupus nephritis is inconclusive based on treatment effects on all-cause mortality, doubling of serum creatinine level, and end-stage kidney disease. MMF, calcineurin inhibitors, or their combination were most effective for inducing remission compared to IV cyclophosphamide, while conferring similar or lower treatment toxicity. MMF was the most effective maintenance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 60 publications
3
64
1
11
Order By: Relevance
“…Type of induction immunosuppressant therapy was not associated with progressive CKD among our patients. This finding is in agreement with a recent meta‐analysis of 53 studies with 4222 participants, which did not find doubling of serum creatinine, ESRD or all‐cause mortality to be different in different therapies . Although not specifically evaluated in LN, protective interventions such as blood pressure control, use of renin–angiotensin–aldosterone system blockers, reduction in dietary protein and sodium and treatment of obesity, dyslipidemia and acidosis have been validated in general CKD cohorts and are relevant and important to the management of patients with LN …”
Section: Discussionsupporting
confidence: 89%
“…Type of induction immunosuppressant therapy was not associated with progressive CKD among our patients. This finding is in agreement with a recent meta‐analysis of 53 studies with 4222 participants, which did not find doubling of serum creatinine, ESRD or all‐cause mortality to be different in different therapies . Although not specifically evaluated in LN, protective interventions such as blood pressure control, use of renin–angiotensin–aldosterone system blockers, reduction in dietary protein and sodium and treatment of obesity, dyslipidemia and acidosis have been validated in general CKD cohorts and are relevant and important to the management of patients with LN …”
Section: Discussionsupporting
confidence: 89%
“…In addition, the recent network meta-analysis mentioned above showed that MMF was the most effective strategy to maintain remission for proliferative LN (44). Studies of proliferative LN in cSLE show similar results for MMF and AZA as in adults.…”
Section: Induction Treatmentmentioning
confidence: 87%
“…They concluded that induction treatment with MMF, CNI, or a combination thereof, when added to corticosteroids, were the most effective treatments compared to I.V. CYC (44). No RCTs have been performed in children, but the literature search yielded several observational cohort studies and case series describing treatment of class III and IV LN.…”
Section: Induction Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…4 They identified 53 studies involving 4222 participants, dividing their analyses into studies evaluating induction-phase treatment (45 trials with 3623 participants) and maintenance-phase treatment (8 trials with 599 participants). The network meta-analysis design allowed these investigators to compare multiple treatment regimens across trials based on a common comparator: intravenous (IV) cyclophosphamide for induction studies and azathioprine for maintenance studies.…”
mentioning
confidence: 99%